2022
DOI: 10.3389/fpls.2022.1038161
|View full text |Cite
|
Sign up to set email alerts
|

A lipidomics platform to analyze the fatty acid compositions of non-polar and polar lipid molecular species from plant tissues: Examples from developing seeds and seedlings of pennycress (Thlaspi arvense)

Abstract: The lipidome comprises the total content of molecular species of each lipid class, and is measured using the analytical techniques of lipidomics. Many liquid chromatography-mass spectrometry (LC-MS) methods have previously been described to characterize the lipidome. However, many lipidomic approaches may not fully uncover the subtleties of lipid molecular species, such as the full fatty acid (FA) composition of certain lipid classes. Here, we describe a stepwise targeted lipidomics approach to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 69 publications
2
9
2
Order By: Relevance
“…Ions m/z corresponding to TAG species are reported in Table 2 along with their fragmentation patterns (MS 2 ). Essentially, the TAG species identified were similar, with some slight variation, to those reported using a reversed-phase HPLC and a triple quadrupole MS technology, (Romsdahl et al, 2022).…”
Section: Identification Of Tag Species By Hptlc-ion Trap Mssupporting
confidence: 77%
See 1 more Smart Citation
“…Ions m/z corresponding to TAG species are reported in Table 2 along with their fragmentation patterns (MS 2 ). Essentially, the TAG species identified were similar, with some slight variation, to those reported using a reversed-phase HPLC and a triple quadrupole MS technology, (Romsdahl et al, 2022).…”
Section: Identification Of Tag Species By Hptlc-ion Trap Mssupporting
confidence: 77%
“…This analytical platform has proven to be useful for lipidomic analysis in complex lipid mixtures (Jarne et al, 2018;Jarne et al, 2021;Sancho-Albero et al, 2022). Our analysis focused on TAGs as it constitutes the major fraction of the total seed lipids in Pennycress (Claver et al, 2017;Romsdahl et al, 2022). Two different lipid extract samples per stage (G, GY, YG, Y and M), which corresponded to two extraction batches, were analyzed by HPTLC-densitometry-MS.…”
Section: Hptlc-esi-ms Characterization Of the Tag Pool Composition Du...mentioning
confidence: 99%
“…reaction monitoring which could be utilized for the targeted characterization of fatty acid profile (Romsdahl et al, 2022).…”
Section: Crop Sciencementioning
confidence: 99%
“…These mutants and genetic regions could be utilized for breeding pennycress lines with desirable oil attributes. Moreover, a recent study developed a comprehensive targeted lipidomics approach to evaluate polar and nonpolar lipid classes using liquid chromatography mass spectrometry and multiple reaction monitoring which could be utilized for the targeted characterization of fatty acid profile (Romsdahl et al., 2022).…”
Section: Trait Improvement Effortsmentioning
confidence: 99%
“…At the molecular level, complete genomic sequencing (Chopra et al, 2018;McGinn et al, 2019;Geng et al, 2021;Garcıá Navarrete et al, 2022;Nunn et al, 2022) and transcriptome assembly of Pennycress genes (Dorn et al, 2013; have been reported, providing tools for its breeding. Other studies have focused in the metabolite profiling of Pennycress seed embryos (Tsogtbaatar et al, 2015;Johnston et al, 2022) or lipidomics (Romsdahl et al, 2022), providing information of lipid species accumulating in its seeds.…”
Section: Introductionmentioning
confidence: 99%